IN SILICO IDENTIFICATION OF NOVEL DRUG TARGETS IN ACINETOBACTER BAUMANNII BY SUBTRACTIVE GENOMIC APPROACH - Goyal, Meenu; Citu, Citu; Singh, Nidhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Multiple drug resistance (MDR) in bacteria, particularly Gram-negative bacilli, has significantly hindered the treatment of infections caused by these bacteria. This results in the need for identifying new drugs and drug targets for these bacteria. The objective of this study was to identify novel drug targets in Acinetobacter baumannii which has emerged as a medically important pathogen due to an increasing number of infections caused by it and its MDR property. Methods: In our study, we implemented in silico subtractive genomics approach to identify novel drug targets in A. baumannii American type culture collection 17978. Various databases and online software were used to build a systematic workflow involving comparative genomics, metabolic pathways analysis, and drug target prioritization to identify pathogen-specific novel drug targets. Results: First, 458 essential proteins were retrieved from a database of essential genes, and by performing BLASTp against Homo sapiens, 246 human non-homologous essential proteins were selected of 458 proteins. Metabolic pathway analysis performed by Kyoto Encyclopedia of Genes and Genomesâ€“Kyoto Automatic Annotation Server revealed that these 246 essential non-homologous proteins were involved in 66 metabolic pathways. Among these metabolic pathways, 12 pathways were found to be unique to Acinetobacter that involved 37 non-homologous essential proteins. Of these essential non-homologous proteins, 19 proteins were found in common as well as unique metabolic pathways and only 18 proteins were unique to Acinetobacter. Finally, these target proteins were filtered to 9 potential targets, based on subcellular localization and assessment of druggability using Drug bank, ChEMBL, and literature. Conclusion: Our study identified nine potential drug targets which are novel targets in A. baumannii and can be used for designing drugs against these proteins. These drugs will be pathogen specific with no side effects on human host, as the potential drug targets are human non-homologous.